1969
DOI: 10.1021/bi00831a041
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial aspartate transaminase. II. Isolation and characterization of the multiple forms

Abstract: Mitochondrial pig heart glutamate-aspartate transaminase (L-aspartate:2-oxoglutarate aminotransferase, E C 2.6.1.1) can be separated by ion-exchange chromatography on carboxymethyl-Sephadex into three fractions each possessing a different electrophoretic mobility. The absorption spectral properties of the fractions have been found to be similar. The subforms are equal in pyridoxal phosphate content, but differ in the relative amounts of "catalytically active" (absorbance at 430 mp at low pH and 360 mp at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
1

Year Published

1970
1970
1998
1998

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 23 publications
5
15
0
1
Order By: Relevance
“…N-terminal amino acid analysis by the dansyl method gave serine as the sole N-terminal residue. In addition, measurements of absorbance due to the protein and to the cofactor at pH 5.4 and pH 8.0 gave values similar to those reported previously for the pure enzyme [24].…”
Section: Purity Of the Enzymesupporting
confidence: 87%
See 1 more Smart Citation
“…N-terminal amino acid analysis by the dansyl method gave serine as the sole N-terminal residue. In addition, measurements of absorbance due to the protein and to the cofactor at pH 5.4 and pH 8.0 gave values similar to those reported previously for the pure enzyme [24].…”
Section: Purity Of the Enzymesupporting
confidence: 87%
“…These represent the so-called subforms of the enzyme [lo]. The origin of the subforms is not clear, but Michuda and Martinez-Carrion [24] have found no chemical differences between them and suggest that they may arise by minor conformational changes. A similar suggestion was made previously [26] to account for the origin of subforms of the cytoplasmic isozyme, although more recently [27] it has been claimed that the subforms differ from one another in the state of amidation of one or more amino acid side chains.…”
Section: Discussionmentioning
confidence: 99%
“…In both tryptophanase (43,44) and tyrosine phenol-lyase (45) from E. coli, cations like K ϩ were shown to induce and stabilize active conformations of these enzymes. With aspartate aminotransferase, at alkaline pH, it was shown that chloride anions (38) as well as dicarboxylic acids (46) can act as competitive inhibitors, possibly by ion pairing with positively charged residues in the active site that serve to bind the ␣-carboxylate group of the substrate.…”
Section: Fig 5 Sds-page Of Human Bcatc Andmentioning
confidence: 99%
“…(d) The concentrations of substrates used throughout these studies were not high enough to form abortive complexes [12]. Further, the isozyme-substrate complexes formed in the preliminary incubation mixtures were as catalytically active as the free isozyme in the assay of residual activity.…”
Section: Isozyrne Preparation and Assaymentioning
confidence: 97%